A meta-analysis of gender differences in volunteers' motivations: sport vs. non-sport events. (19th November 2019) - Park, Sanghyun; Won, Doyeon; Shonk, David J.
The current study meta-analytically examined empirical studies to assess the gender differences in volunteer motivation, using the volunteer function inventory (VFI), and investigated the moderating effect of volunteering context (sport vs. non-sport events) on the relationship between volunteer gender and motivation. A total of 19 studies, published from 2007 to 2017, met the inclusion criteria, and were reviewed by two readers. Cohen's Kappa was calculated for the reliability between the two coders and all meta-analyses were conducted using the comprehensive meta-analysis (CMA) program. Results from this meta-study suggested that women scored higher than men on three of the six subscales of the VFI instrument, particularly social, understanding and value-related motivation. Moderator analyses indicated the type of volunteering context is a meaningful moderator of the relationship between gender and motivation. The results also suggested the volunteering context influenced the magnitude and direction of gender differences in all motivational dimensions, except social motivation.